Diversity of root system of Lucerne populations - О. Д. Тищенко; Л. В. Андрусіва; Я. М. Рибалко (Plant Varieties Studying and Protection)
It is stated that morphological structure of Lucerne root system has significant influence on productivity raising of its overground and root-like substances.